Image segmentation: the case of Taman Negara Pahang / Anizah Zainuddin … [et al.] - Zainuddin, Anizah; Zahiruddin, Zubaidah; Abu Bakar, Kalsom; Ismail, Noor Afizah (Research Management Institute (RMI), 2011)
The purpose of this study is to segment the tourism industry market specifically in Taman Negara Pahang, Malaysia (TNP); into consumer groups based on their images of a tourism destination. The objective is to identify segments which offer more favorable images. This is because, positive image will increases the likelihood of visitation, thus present the most significant target markets to the tourism marketers and service providers. 250 questionnaires were distributed with the purpose of assessing local and foreign travelers' image of TNP as a vacation destination. The questions asked utilized using five point Likert scale and consisted of four components involving socio-cultural amenities, natural amenities, participative recreational activities and climate. The respondents were analytically grouped into distinct segments based on their favorable and unfavorable images. Respondents with a similar and different expression on the variables were grouped together. The identified segments were then, described in terms of their image content and were profiled with demographic characteristics. This study was concluded with recommendations of appropriate policies to the relevant authorities for making development decisions in the near future.